Penerapan Kepemimpinan Alkitabiah Dalam Pertumbuhan Jemaat di GESBA The Newlife Jakarta - Toding, Sarah Priska; Widodo, Jusuf Agustian; Baringbing, Pangeran Guntar Wijaya; Tneh, Yared Efriadi; Nendissa, Julio Eleazer (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2025)
Biblical leadership plays a crucial role in the development of church congregations. At GESBA The Newlife Jakarta, leadership principles based on Biblical teachings serve as the main guide in shaping the character and spirituality of the congregation. This article aims to explore the application of Biblical leadership in the context of congregation growth at the church. The research uses a qualitative approach with a descriptive method, involving data collection through interviews and observations. The collected data will be analyzed using a thematic approach to identify patterns, categories, and relationships within the data. The analysis steps include critically reviewing literature, grouping information based on key themes such as the application of Biblical teachings, congregation growth, and interpreting findings based on supporting theories. The primary focus of this research is on how Biblical leadership values, such as service, humility, and the encouragement for spiritual growth, are applied by church leaders in guiding the congregation toward spiritual maturity. The research findings show that leadership based on Biblical teachings not only impacts the personal spirituality of leaders but also creates an environment that supports collective congregation growth. Leaders at GESBA The Newlife Jakarta apply the principles of love, deep teachings, and service with a caring heart, which has proven to accelerate faith growth and congregation engagement in church activities. This article also identifies the challenges faced in implementing Biblical leadership in the modern era and how church leaders are addressing them. It is hoped that the findings of this study can provide insights for other churches in developing healthy and effective leadership models according to Biblical teachings, and serve as an inspiration for more qualitative congregation growth in the future.